2015
DOI: 10.1590/0102-311x00169913
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 10-valent pneumococcal conjugate vaccine on pneumococcal meningitis in children up to two years of age in Brazil

Abstract: The objective of this study was to analyze the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Before-after was the most common study design, and surveillance the most common data source used in the reported studies (Table 1). A total of 6 studies analyzed mortality: 2 evaluated PCV impact on pneumococcal meningitis deaths [19, 20], 2 evaluated impact on all-cause deaths [21, 22], and 3 analyzed deaths due to pneumonia [2224]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before-after was the most common study design, and surveillance the most common data source used in the reported studies (Table 1). A total of 6 studies analyzed mortality: 2 evaluated PCV impact on pneumococcal meningitis deaths [19, 20], 2 evaluated impact on all-cause deaths [21, 22], and 3 analyzed deaths due to pneumonia [2224]. …”
Section: Resultsmentioning
confidence: 99%
“…They comprised four before-after [19, 20, 41, 42], and one case-control study [15]. Hospitalization rates before intervention reported in the before–after studies were higher among younger children, varying from a lower 0.83/100,000 in children aged 2–3 years [20] to 14.85/100,000 in infants <1 year old [19]. (Table 3)…”
Section: Resultsmentioning
confidence: 99%
“…In 2010, Hanquet and colleagues proposed to initially focus on the collection and analysis of meningitis data from all countries as a minimum common data set, as one of the considerations for establishing a uniform European IPD surveillance system 47 . In some countries however, PCV use had variable influence on the rate of pneumococcal meningitis; while a decrease in pneumococcal meningitis morbidity and mortality rates was reported in Brazil after introduction of PHiD-CV, 48 another study reported large confidence intervals, 49 and in several countries, only a slight decrease in pneumococcal meningitis cases after PCV13 implementation was observed 50 . This variability could increase the difficulty to estimate the potential impact of vaccination on pneumococcal disease, when based solely on meningitis data.…”
Section: Resultsmentioning
confidence: 99%
“…12 Similar result was demonstrated against pneumococcal meningitis in children 2 years of age using before-and-after methodology. 13 Both studies were conducted in Brazil between 2007 and 2012.…”
Section: Introductionmentioning
confidence: 99%